2006
DOI: 10.1016/j.juro.2006.03.062
|View full text |Cite
|
Sign up to set email alerts
|

Urgency is the Core Symptom of Female Overactive Bladder Syndrome, as Demonstrated by a Statistical Analysis

Abstract: We used statistical analysis to determine and suggest that urgency is the core symptom of female overactive bladder syndrome and there are 3 distinctive overactive bladder subtypes, which differ in their symptom combinations. Different symptom combinations and patient characteristics affect female adaptation to overactive bladder syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 21 publications
1
26
0
Order By: Relevance
“…14 Studies suggest that urgency is the core symptom of OAB in women. 15 However, urgency is not specific to any clinical entity, and can be the primary symptom in women with interstitial cystitis/painful bladder syndrome, OAB with leakage (OAB-wet), and OAB without leakage (OAB-dry). Some experts believe that it is appropriate to include both OAB-dry groups, those with fear of leakage and those with uncomfortable urge under the OAB umbrella.…”
Section: Discussionmentioning
confidence: 99%
“…14 Studies suggest that urgency is the core symptom of OAB in women. 15 However, urgency is not specific to any clinical entity, and can be the primary symptom in women with interstitial cystitis/painful bladder syndrome, OAB with leakage (OAB-wet), and OAB without leakage (OAB-dry). Some experts believe that it is appropriate to include both OAB-dry groups, those with fear of leakage and those with uncomfortable urge under the OAB umbrella.…”
Section: Discussionmentioning
confidence: 99%
“…In one of our previous manuscripts, published in 2006, we conducted a survey of hospital‐based female patients and found that no single or isolated symptom presented in patients with OAB. We found that OAB patients could be categorized into three groups, that is, patients with dry symptoms (urgency, frequency, and nocturia), patients with wet symptoms (urgency, urge incontinence, and mixed incontinence) and a small group with OAB symptoms combined with voiding difficulty symptoms 6…”
Section: Introductionmentioning
confidence: 99%
“…For example, women with voiding dysfunction may also have the symptom of urgency, which is the core symptom of overactive bladder syndrome (OAB) [2]. Symptom-based treatment may lead to ineffectiveness and drug-related adverse effects, such as dry mouth, pruritus, and constipation after antimuscarinic treatment [3].…”
Section: Introductionmentioning
confidence: 99%